Study on Species Diversity and Stand Structure in Meru Betiri National Park - Heru Dwi Riyanto; Agus Wuryanta (Forum Geografi, 2015)
National parks are forest ecosystems that contain biotic and abiotic resources. Biodiversity is the data and information necessary to understand the degree of loss of species diversity and formulate a sustainable alternative of decline in these resources. The research objective is to study the reciprocal relationship between elevation and habitat of a species in an ecosystem. Research conducted at the National Park (TN) Meru Betiri. The results show that there are spatial variabilities of the species diversity based on the elevation in the study area. Elevation is inversely proportional to species diversity index, the higher the elevation, the species diversity index tends to decline, but the index of the importance of endemic species have increased. Group stand structure and species composition is influenced by the level of elevation with their own environment.